United Kingdom-Hong Kong : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper reviews the key institutions and arrangements for economic policymaking that were expected to be put in place following the transfer of sovereignty over Hong Kong to China in 1997. International treaties between Britain and China from the nineteenth century are reviewed. The paper discusses Hong Kong's current and future constitutional documents-the Letters Patent and Royal Instructions, and the Basic Law, respectively. The paper also provides a background on the system of government in Hong Kong in 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet